Local Experience: Battling for CAPD in Pakistan: The Shifa Experience - Khurshid, Kiran (Pakistan Journal of Kidney Diseases, 2021)
Peritoneal Dialysis (PD) is recognized as a patient centered modality for End Stage Kidney Disease worldwide. Compared to In-Centre Hemodialysis, it gives the patients a better quality of life. Rather than urgent start, 2 weeks rest after placement of PD catheter is preferred to avoid leaks. Since I joined Shifa International hospital Islamabad, Pakistan, a gradual increase in CPAD population was seen. We share our experience and discuss the issues faced.